2015
DOI: 10.2147/ott.s92314
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125a-5p regulates cancer cell proliferation and migration through NAIF1 in prostate carcinoma

Abstract: BackgroundWe investigated the functional roles of microRNA-125a-5p in regulating human prostate carcinoma.MethodsQuantitative reverse transcription-polymerase chain reaction (qRT-PCR) was conducted to evaluate the gene expression levels of miR-125a-5p in eight prostate cancer cell lines and nine biopsy specimens from patients with prostate cancer. miR-125a-5p was genetically knocked down in prostate cancer cell lines, DU145 and VCaP cells by lentiviral transduction. The effects of miR-125a-5p downregulation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
(16 reference statements)
1
39
0
Order By: Relevance
“…The increased methylation of miR-125a promoter may lead to a decrease in transcription factor recruitment to the promoter, thus resulting in a decrease in the expression of miR-125a. Previous studies have shown that miR-125a plays a role as a tumor suppressor genes in prostate cancer [15], glioblastoma [16, 17], breast cancer [18], liver cancer [7, 19], gastric cancer [11, 20] and cervical cancer [21, 22]. Wang et al found that EGFR inhibited the invasion of lung cancer cells by activating miR-125a, and miR-125a could also inhibit the proliferation of vascular endothelial cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…The increased methylation of miR-125a promoter may lead to a decrease in transcription factor recruitment to the promoter, thus resulting in a decrease in the expression of miR-125a. Previous studies have shown that miR-125a plays a role as a tumor suppressor genes in prostate cancer [15], glioblastoma [16, 17], breast cancer [18], liver cancer [7, 19], gastric cancer [11, 20] and cervical cancer [21, 22]. Wang et al found that EGFR inhibited the invasion of lung cancer cells by activating miR-125a, and miR-125a could also inhibit the proliferation of vascular endothelial cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…The human gene encoding nuclear apoptosis‐inducing factor 1 (NAIF1) is located on chromosome 9q34.11, and reported to repress the progression of several human cancers . NAIF1 was downregulated or lost in gastric cancer tissues, plays an inhibitory role in the initial steps of gastric cancer genesis .…”
Section: Introductionmentioning
confidence: 99%
“…NAIF1 was downregulated or lost in gastric cancer tissues, plays an inhibitory role in the initial steps of gastric cancer genesis . Fu et al showed that overexpression of NAIF1 had an antitumor effect on prostate cancer cell proliferation and migration . NAIF1 expression level in NSCLC tissues was suppressed, and restoration of NAIF1 in lung cancer cell inhibited cell proliferation and anchorage‐independent survival ability .…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulated miR-125a was also reported in prostate cancer [71]. However, other studies have reported under-expression of miR-125a and suggested a tumor suppressive role for this miRNA [72][73][74][75].…”
Section: Figurementioning
confidence: 87%